2012
DOI: 10.1371/journal.pone.0048605
|View full text |Cite
|
Sign up to set email alerts
|

FABP4 Dynamics in Obesity: Discrepancies in Adipose Tissue and Liver Expression Regarding Circulating Plasma Levels

Abstract: BackgroundFABP4 is predominantly expressed in adipose tissue, and its circulating levels are linked with obesity and a poor atherogenic profile.ObjectiveIn patients with a wide BMI range, we analyze FABP4 expression in adipose and hepatic tissues in the settings of obesity and insulin resistance. Associations between FABP4 expression in adipose tissue and the FABP4 plasma level as well as the main adipogenic and lipolytic genes expressed in adipose tissue were also analyzed.MethodsThe expression of several lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 43 publications
2
51
2
5
Order By: Relevance
“…Supporting these assumptions, we did not observe significant differences between groups in mRNA level of markers of nonadipocyte cells, suggesting no interference of other cell types with the DNA quantification procedure. Furthermore, the decreased Fabp4 expression in mice receiving the HF-D diet is in agreement with an IR state, fat cell hypertrophy, and changes in body composition as described in humans (25,26).…”
Section: Figsupporting
confidence: 82%
“…Supporting these assumptions, we did not observe significant differences between groups in mRNA level of markers of nonadipocyte cells, suggesting no interference of other cell types with the DNA quantification procedure. Furthermore, the decreased Fabp4 expression in mice receiving the HF-D diet is in agreement with an IR state, fat cell hypertrophy, and changes in body composition as described in humans (25,26).…”
Section: Figsupporting
confidence: 82%
“…FABP4 is one of the most abundant proteins in mature adipocytes and is also detected at high concentrations in human serum. Although the biological role of FABP4 is not fully understood, it has been linked to insulin sensitivity, lipid metabolism, and inflammation [46]. Previously, we have shown that FABP4 levels are elevated in obese and diabetic individuals, and such increased levels are closely correlated with adverse lipid profiles, insulin resistance, and vascular smooth muscle cell proliferation [47,48,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the insulin-resistant state, which is a condition often associated with central obesity, adipocyte lipolysis increases regardless of nutritional fluctuations, leading to the release of abundant FFAs into the blood [12]. In the liver, several membrane-bound proteins are responsible for transporting circulating FFAs into hepatocytes, including fatty acid transporter protein (FATP)-2 [15], FATP-5 [16], fatty acid translocase (FAT/CD36) [17][18][19], caveolins [20,21], fatty acid binding proteins (FABP)-1, FABP-4, and FABP-5 [22,23]. Upregulation of several FFA transporters is associated with increased insulin resistance and hepatic steatosis in NAFLD patients [24][25][26][27].…”
Section: Increased Hepatic Fatty Acid Uptakementioning
confidence: 99%